PENDAMPINGAN PENYUSUNAN PERANGKAT PEMBELAJARAN MENGGUNAKAN BANTUAN ARTIFICIAL INTELLIGENCE (AI) - Mulyatiningsih, Endang; Kharismawati, Anisa; Trilisiana, Novi (Universitas Mataram, 2025)
The rapid advancement of information and communication technology has had a significant impact on various aspects of life, including the education sector. One of the technological innovations that has attracted increasing attention is Artificial Intelligence (AI). However, its utilization in education, particularly in the development of learning materials, is still not optimal. Vocational and high school teachers at the LP Ma’arif NU PWNU DIY Foundation strive to keep up with technological developments by utilizing AI tools that can be applied in the preparation of learning devices. This activity aimed to provide training and assistance to teachers in using AI tools, including preparing learning materials, designing instructional media, and creating AI-based quizzes and interactive games. Through this program, it is expected that teachers’ ability to develop more varied and effective learning devices will improve. The implementation of this activity consisted of four stages. The first stage was lectures and discussions to provide basic understanding of AI concepts and benefits in education. The second stage involved training on the use of AI tools for developing learning materials. The third stage was practical mentoring. The final stage was an evaluation to measure participants’ understanding and skills after the program. The evaluation results showed an increase in participants’ understanding of AI tools. In addition, participants’ interest and confidence in utilizing AI for learning, which was already high, increased further after the training. Thus, this program proved effective in improving teachers’ knowledge, skills, and motivation to integrate AI into the teaching and learning process.